Electric bus fleets during urban flash floods: A mixed bus fleet strategy - Sanghuiyu Yan; Pengju Ren; Guohong Wu; Jian Li (International Journal of Transportation Science and Technology)
Bus electrification is widely cited as a key technique to reduce carbon emissions and mitigate climate change. In some Chinese cities, the electrification rate of buses has even reached 100%. However, compared with diesel buses (DBs), electric buses (EBs) cause scheduling problems during urban flash floods due to their limited wading performance. This study proposes a mixed EB-DB fleet strategy to mitigate bus fleet problems during urban flash floods. The difference in wading height thresholds between EBs and DBs is considered in the fleet schedule. Utilizing a two-fleet strategy, the requisite number of DBs for bus depots is calculated. The mixed bus assignment problem is then solved by linear programming to establish the optimal dispatch scheme for the individual bus route. This study emphasizes the advantages of mixed bus fleets in emergency response, and contributes to improving urban transportation resilience.